(3efXheI aj Yde MSGH GdYbhOs - (3CHj GdMSf Ydj, GHf GdeZQHjs ((3eMeO Hf eMeO Hf GdNGUQi s)
(3ChdgG (B:s
(3eWdYgG jbhd QGLi Gddg efTF GdSMH Ydi GdeYQha HGHf GdeZQH s
(3BNQgG (B:s
(3hPGc CbUi eG jQGe YfOg hjSJWGY HGdjOjf YOg s
(3Vef eLehY s
(3JHUQI GdYfhGf (B:s
(3fXe s
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B1020 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B94 s
(3eUOQ GbJfGA GdCUd (B:s
(3Yehejg (B(1088) s
Keywords: (3GdQjGVjGJs